INTEGRASI-INTERKONEKSI DALAM STUDI HADIS DISERTASI DI UIN SUNAN KALIJAGA YOGYAKARTA - Lukman, Fadhli (RELIGIA, 2016)
Amin Abdullah introduced integrative-interconnective paradigm in State Islamic University Sunan Kalijaga Yogyakarta in order to develop Islamic studies. The main character of this paradigm is the willingness to consider the visibility of various approaches form outside conventional Islamic sciences, mainly from social and humanistic approaches. This article intend to see the application of integrativeinterconnective paradigm in UIN Sunan Kalijaga through the doctoral disertation on hadith studies. Analysing the methodological aspect of the disertations, the article ends up to a notion that integrative-interconnective paradigm is reflected within nine of fourteen dissertation under discussion.